Correlation of Air, Surface and Pavement Temperatures using MPU 6050 Accelerometer Sensor - Septiani, Teni; HM, Muhamad Rofi; Syafier, Siegfried; Utomo, Eko Wahyu (Universitas Negeri Padang, 2024)
This research analyses the correlation between air temperature, road surface temperature and pavement temperature using the MPU 6050 accelerometer sensor and the Pearson correlation method. Temperature measurements were taken at several predetermined locations, with the data analysed to identify the correlation between the three types of temperature. The analysis showed a very strong correlation between air temperature and road surface temperature, with a correlation coefficient of 0.7845 at night and 0.9663 during the day. Similarly, there is a very strong correlation between road surface temperature and pavement temperature, with a correlation coefficient of 0.8482 at night and 0.9673 during the day. These findings indicate that an increase in road surface temperature leads to an increase in pavement temperature. It was concluded that the correlation method can be used to predict temperatures at other points without invasive direct measurements, thus preventing damage to the road due to destructive measurements. This method is recommended as an alternative in pavement temperature monitoring.